Cystic Fibrosis: Its Impact at Women’s Fertility and their Pregnancy. A Narrative Review - C. Loukopoulou; F. Gkrozou; A. Geroula; N. Mantzoukidou1; A. Zoi; C. Skentou; A. Vatopoulou; O. Tsonis (British Journal of Healthcare and Medical Research, 2023)
Women with cystic fibrosis (CF) leave more years than in the past. This is the reason why this population has increased expectations for a more “normal” life. We aimed to assess current maternal and fetal outcomes in women with CF with varied pre-pregnancy lung function, in addition with fertility outcome after artificial reproductive technology (ART). A review of relative literature was conducted, using the MEDLINE database, the ScienceDirect database and Google scholar and relevant keywords. Studies confirmed that more women with CF are considering pregnancy. Unplanned pregnancies also are happening, and women need the right guidance. Most women will have normal pregnancies, but preterm births are common. Optimization of treatment is recommended during family planning or pregnancy. Reduced fertility may be overcome with ART. With careful multidisciplinary antenatal and intrapartum management, successful outcomes have been obtained in women with CF.